Drip irrigation technology in Karnataka, India - Rashmi Shivamurthy Kabbur; Stijn Speelman; Gonzalo Gabriel Villa Cox (Agricultural Economics Research Review, 2023)
This study assesses whether the practice of drip irrigation in Karnataka reduced the usage of groundwater. It finds that while drip irrigation does reduce the quantity of groundwater used per acre, the quantity of the groundwater used per farm does not fall concomitantly, because the irrigation intensity of drip irrigation is greater. Therefore, limiting the area under drip irrigation would make the adoption of the technology sustainable and address food security, and the government should complement the practice of drip irrigation. There is no rebound effect or instance of the Jevons paradox.